Bioactive components of red seaweeds: A promising source for therapeutic uses in the future - Samira El Majnaoui; Mounia Lekrati; Ahmed Belmouden; Hind Dehbi; Joumana El Turk; Abbdellah Houari; Nadia El Kadmiri (Journal of Biological Research)
Seaweed grows and reproduces in intertidal and subtidal regions where photosynthesis is possible due to the available lighting. Marine macroalgae are classified into three main groups according to their pigment content: red algae (Rhodophyceae), green algae (Chlorophyceae), and brown algae (Phaeophyceae). They are becoming a valuable resource and are distinguished by their rapid growth capacity with high nutritional value. Red algae contain a wide variety of biochemical substances, including: phenolics, polysaccharides, proteins bromophenols, pigments, low amounts of fatty acids, and they are essentially the only species capable of producing long-chain Polyunsaturated Fatty Acids (PUFAs), vitamins specially B12, minerals. Those compounds have anti-tumor, antioxidant, anti-inflammatory, antibacterial, and antiviral properties. Additionally, seaweeds have an excellent nutritional profile highly supplying macro and micro nutrients; thus, they can be used as food in diets. They can also be an essential source of novel pharmaceutical and therapeutic compounds. This review summarizes the potential of the bioactive substances obtained from diverse red seaweeds around the world, which are expected to be promising components for application in the medical industry. The pharmaceutical industry could use red seaweeds to prevent or treat several illnesses, including: cancer, obesity, and other chronic diseases, as their medicinal benefits are considerably more intriguing than their purely nutritional advantages. Novel natural drugs developed from algae could act as alternatives for artificial substances in the future.